Kinetic H2S/CO2 selectivity in an exceptionally sterically hindered amine membrane - Rao, Shraavya; Deng, Xuepeng; Zou, Changlong; Prasad, Babul; Han, Yang; Lin, Li-Chiang; Ho, W. S. Winston (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: Absorption; COMPOSITE MEMBRANES; GAS STREAMS; H2S; Thin-Film

Carbon capture from flue gases using an integrated membrane skid - Yang, Yutong; Han, Yang; Prasad, Babul; Pang, Ruizhi; Zou, Changlong; Ho, W. S. Winston (Journal of Membrane Science, 2025)
A prototype spiral-wound (SW) membrane module with a commercial-size diameter of 8 `' and a membrane area of 35 m(2) was fabricated using a new thin-film-composite facilitated transport membrane (FTM) scaled up to 21 `' in width by a continuous roll-to-roll coating process. This SW module was tested with an actual coal flue gas at the Center for Applied Energy Research (CAER) at the University of Kentucky, which exhibited an average CO2 permeance of 4269 GPU with a CO2/N-2 selectivity of 165 and remained stable for 100 h. The permeance and selectivity results are consistent with those determined from lab and scale-up flat-sheet samples. An integrated membrane skid was then constructed, where 2 SW membrane modules were arranged to form an enriching cascade. The 8 `'-diameter prototype SW module previously tested at CAER was installed as the primary CO2 capture stage, while a smaller SW module (5 `' diameter and 12 m(2) membrane area) was used to further enrich the CO2 to >95% purity. By using a simulated coal flue gas (13% CO2), the skid was operated at steady-state for 800 h with 91.0% of the CO2 removed from the flue gas, delivering 1.33 tonne/day CO2 product at 95.5% dry purity. The bench skid was then installed at the National Carbon Capture Center (NCCC), Wilsonville, AL and tested with an actual natural gas (NG) flue gas (8.6% CO2). 90-99% CO2 capture degrees were demonstrated during the parametric testing, and the skid was operated at steady state for 500 h cumulatively with 91.0% CO2 capture and >95% CO2 purity. A simulated natural gas combined cycle (NGCC) flue gas (4.3% CO2) slipstream was further provided by diluting the NG flue gas with air, and 90-99% CO2 capture degrees were also achieved with dry CO2 purities all above 95%. All these capture degrees and CO2 purities were in good agreement with their model predictions.
Keywords: Actual flue gas; carbon capture; Field trial; Integrated membrane skid; Membrane module